Janus-faced myeloid-derived suppressor cell exosomes for the good and the bad in cancer and autoimmune disease - Zöller, Margot (Frontiers in immunology, 2018)
Myeloid-derived suppressor cells (MDSC) are a heterogeneous population of immature myeloid cells originally described to hamper immune responses in chronic infections. Meanwhile they are known to be a major obstacle in cancer immunotherapy. On the other hand, MDSC can interfere with allogeneic transplant rejection and may dampen autoreactive T cell activity. Whether MDSC-Exosomes (Exo) can cope with the dangerous and potentially therapeutic activities of MDSC is not yet fully explored. After introducing MDSC and Exo, it will be discussed, whether a blockade of MDSC-Exo could foster the efficacy of immunotherapy in cancer and mitigate tumor progression supporting activities of MDSC. It also will be outlined, whether application of native or tailored MDSC-Exo might prohibit autoimmune disease progression. These considerations are based on the steadily increasing knowledge on Exo composition, their capacity to distribute throughout the organism combined with selectivity of targeting and the ease to tailor Exo and includes open questions that answers will facilitate optimizing protocols for a MDSC-Exo blockade in cancer as well as for strengthening their therapeutic efficacy in autoimmune disease.